Сказать - не сказать...: рассказы и повести / Виктория Токарева - Токарева Виктория Самойловна (Азбука, 2015)
Экземпляры: ф.4 (20181022) / Инвентарный номер: 43175 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Т 51 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6